Searching where Ideas Are Harder to Find – The Productivity Slowdown as a Result of Firms Hindering Disruptive Innovation - Richard Bräuer (Halle Institute for Economic Research (IWH), 2024)
This paper proposes to explain the productivity growth slowdown with the poaching of disruptive inventors by firms these inventors threaten with their research. I build an endogenous growth model with incremental and disruptive innovation and an inventor labor market where this defensive poaching takes place. Incremental firms poach more as they grow, which lowers the probability of disruption and makes large incremental firms even more prevalent. I perform an event study around disruptive innovations to confirm the main features of the model: Disruptions increase future research productivity, hurt incumbent inventors and raise the probability of future disruption. Without disruption, technology classes slowly trend even further towards incrementalism. I calibrate the model to the global patent landscape in 1990 and show that the model predicts 52% of the decline of disruptive innovation until 2010.
Keywords: J24; J42; J44; O12; O33; O41; 330; disruptive innovation; general equilibrium; general purpose technology; growth; innovation strategies; inventor labor market